Immunogenetics and rheumatic diseases: 25 years on from HLA-B27 - Wordsworth, P (1999)
· The strong HLA associations of many inflammatory arthropathies imply an underlying autoimmune pathology. · The function of HLA molecules in the recognition of viral and bacterial antigens is now well described and has important implications for the pathogenesis of diseases such as ankylosing spondylitis, reactive arthritis and rheumatoid arthritis. · HLA-B27 is strongly associated with ankylosing spondylitis and has played an important role in defining a group of related spondyloarthropathies. · HLA genes contribute less than half of the genetic basis of these diseases. · Whole genome screening is a power tool to detect other genes relevant to these conditions.